Answer:
lol fr
Step-by-step explanation:
Answer:
4262
Step-by-step explanation:
2 + 7x^2- 2x^3-8x +7x^4 at x = 5
= 2 + 7*(5)^2 - 2*(5)^3-8*5 +7*(5)^4
=2+175-250-40+4375
=4552-290
=4262
Answer:
1091750
Step-by-step explanation:
if your dividing
Step-by-step explanation:
first step is to find the gradient of the line which "m" on the equation
gradient formula is y2 - y1 ÷ x2 - x1 = -½ as shown on the picture we substituted those points given
2nd step is to substitute on the equation y=mx+c
m= -½
y= 3 (you can choose any from those given points but in my case I chose point A)
x= -2
c= ? only unknown variable so we can can calculate it
substitute as shown on the picture to get c= 2
therefore our equation of the line will be y= -½x+2
Answer:
z ≤ 6
Explanation:
z is less than or equal to: z ≤
z is less than or equal to six: z ≤ 6